A VHDL implementation of onu auto-discovery process for EPON - Mady, A.E.-D.; Tonini, A. (2009 International Conference on Networking and Media Convergence, 2009)
Recently EPON has been appeared to introduce the convergence of low-cost Ethernet equipment and fiber infrastructure, it is appeared to be the best candidate for the next-generation access network. Auto-discovery process is an important process in EPON system. . Indeed, this paper provides a MAC design following the IEEE 802.3ah standard of the MPCP auto-discovery process at the ONU side. It describes as well the validation and verification steps using an OLT model and finally, the synthesis result are presented.